STRATEGI PENGEMBANGAN MUSEUM DAYU SEBAGAI SARANA WISATA EDUKASI - Iwan Wahyu Dwitama; Argyo Demartoto (Universitas Sebelas Maret (UNS), 2019)
The museum functions as a management of cultural heritage which actually has the same ideology as cultural tourism, namely providing information and services to the public. The museum not only collects material culture and daily social history but also includes collecting human behavior. The museum also functions as an educational tourism choice that has not been done much by the community. The purpose of this study was to find out more about the strategy of developing the Dayu museum as an educational tourism object. This research uses Structural Fungtionalism theory from Talcott Parsons, the method of data collection is done by conducting observations, interviews and documentation. Data validity was done by triangulation techniques, namely data triangulation, source triangulation, methodological triangulation, researcher triangulation, and theory triangulation. The results of the study show that officers from both the museum and the tourism service provide education especially to the surrounding community. Regional mapping is done to find out the potential of the village wilaya. Potential will be developed in a sustainable manner to increase income and advance rural areas. With the establishment of the Dayu museum on an international scale, the tour becomes a world heritage. The perceived impact of the formation of tourism internationally, it will increase the independence of the surrounding community. The use of information media as a means of marketing products is done both traditionally and modernly. Traditionally by texting, officers came to various schools to conduct socialization. Whereas in a modern way it is done by making museum videos conducted by the Karanganyar Regency government.